KLASIFIKASI JUMLAH KENDARAAN DI SUMATERA UTARA DAN SUMATERA BARAT MENGGUNAKAN ALGORITMA NAIVE BAYES - Andy Tessa Saragih; Dwi Afrida; R. Fazlun Dinara (LPPM STMIK Royal Kisaran, 2023)
Abstract : The Central Bureau of Statistics (BPS) is a non-departmental government agency established as a provider of data or information based on Law No. 6/1960 on Census and Law No. 7/1997 on Statistics. The Central Statistics Agency (BPS) recorded the number of motorized vehicles such as cars, buses, trucks, and motorcycles in the provinces of North Sumatra and West Sumatra in 2020-2021 reaching 3,043,892 million units. The purpose of this study is to classify the number of motorized vehicles in the form of cars, motorcycles, buses and trucks. This research uses quantitative research with Naive Bayes Algorithm analysis model. The data used in this study is data from several regions in North Sumatra Province and West Sumatra Province in 2020-2021. Evaluation of model performance is based on accuracy parameters, precision and total recall of the confusion-matrix. The results of testing the dataset and calculating the model performance parameters have obtained an accuracy value of 100%. With the percentage value of the description of each dataset class, namely a little 70.6%, moderate 21.6%, and a lot 7.8%. Keywords :classification;confusion-matrix; data; motor vehicles; naive bayes Abstrak : Badan Pusat Statistik (BPS) adalah lembaga pemerintahan non-departemen yang dibentuk sebagai penyedia data atau informasi berdasarkan UU Nomor 6 Tahun 1960 tentang Sensus dan UU Nomor 7 Tahun 1997 tentang Statistik. Badan Pusat Statistik (BPS) mencatat jumlah kendaraan bermotor seperti mobil, bus, truk, dan sepeda motor di Provinsi Sumatera Utara dan Sumatera Barat pada tahun 2020-2021 mencapai 3.043.892 juta unit. Tujuan dari penelitian ini yaitu untuk mengklasifikasikan jumlah kendaraan bermotor berupa mobil, sepeda motor, bus dan, truk. Adapun penelitian ini menggunakan jenis penelitian kuantitatif dengan model analisis Algoritma Naive Bayes. Data yang digunakan pada penelitian ini adalah data dari beberapa daerah di Provinsi Sumatera Utara dan Provinsi Sumatera Barat tahun 2020-2021. Evaluasi kinerja model didasarkan pada parameter akurasi, presisi dan recall total dari Confusion-Matrix. Hasil pengujian dataset dan perhitungan parameter performa model telah didapat nilai akurasi 100%. Dengan presentase nilai keterangan setiap kelas dataset yaitu Sedikit 70,6%, Sedang 21,6%, dan Banyak 7,8%. Kata kunci :confusion-matrix; data; kendaraan bermotorklasifikasi; naive bayes